Citizen observatory based soil moisture monitoring – the GROW example - KovácsKároly Zoltán; Hemment, Drew; Woods, Mel; VeldenNaomi K. van der; Xaver, Angelika; GiesenRianne H.; BurtonVictoria J.; GarrettNatalie L.; Zappa, Luca; Long, Deborah; Dobos, Endre; Skalsky, Rastislav (Hungarian Geographical Bulletin, 2019)
GROW Observatory is a project funded under the European Union’s Horizon 2020 research and innovation program. Its aim is to establish a large scale (more than 20,000 participants), resilient and integrated ‘Citizen Observatory’ (CO) and community for environmental monitoring that is self-sustaining beyond the life of the project. This article describes how the initial framework and tools were developed to evolve, bring together and train such a community; raising interest, engaging participants, and educating to support reliable observations, measurements and documentation, and considerations with a special focus on the reliability of the resulting dataset for scientific purposes. The scientific purposes of GROW observatory are to test the data quality and the spatial representativity of a citizen engagement driven spatial distribution as reliably inputs for soil moisture monitoring and to create timely series of gridded soil moisture products based on citizens’ observations using low cost soil moisture (SM) sensors, and to provide an extensive dataset of in situ soil moisture observations which can serve as a reference to validate satellite-based SM products and support the Copernicus in situ component. This article aims to showcase the initial steps of setting up such a monitoring network that has been reached at the mid-way point of the project’s funded period, focusing mainly on the design and development of the CO monitoring network.